The productive mind: Creativity as a source of abstract mental representations. (19th June 2020) - Fedyk, Mark; Xu, Fei
Abstract: Explanations of how the brain makes successful predictions should refer to abstracta. But, the mind/brain system is for more than prediction alone. Creativity also plays an important role in supply the mind/brain system with abstracta that serve a number of valuable ends over and above prediction.